PROPRIEDADES ELETRÔNICAS E DE TRANSPORTE EM NANOFITAS DE FOSFORENO NEGRO E BOROFENO β12 - Ledur, Cristian Mafra (2021)
Nanotechnology has attracted the interest of many research groups due to the ability of some materials to present anisotropic properties with the modulation in material’s scale. Phosphorus (P) has several allotropic structures due to its five electrons in the valence shell. The most famous phosphorus’ allotropes are the white phosphorus, red phosphorus and black phosphorus. Two more recently known allotropes are the black and blue phosphorene, two-dimensional (2D) structures, which confine the movement of electrons in the thickness direction. Boron (B) has also been emerging due to some of its 2D allotropes: the β12 and χ3 borophene structures. These structures (phosphorene and borophene) have shown characteristics that encourage researchers involved, noting that both have already been obtained experimentally. This work aims to study black phosphorene and β12 borophene nanoribbons, one-dimensional (1D) structures, from computational simulation calculations using the SIESTA computational code and the Density Functional Theory (DFT) to obtain information related to the nanoribbons’ structural, electronic and magnetic properties and, TRANSiesta in obtaining data related to electronic transport. Phosphorus nanostructures were studied in its pristine and Si-doped configurations, while boron only pristine. β12 borophene keeps its metallic characteristics regardless of the nanoribbons width. Moreover, these nanoribbons are likely to transmit electrons through pore and edge atoms. Phosphorene structures show the ability to identify the amino acid molecules separately. The data show that black phosphorene and β12 borophene are promising structures when used as base material for BCAA sensors.